2015
DOI: 10.1039/c5ra11346f
|View full text |Cite
|
Sign up to set email alerts
|

Computational evidence to design an appropriate candidate for the treatment of Alzheimer's disease through replacement of the heptamethylene linker of bis(7)tacrine with S-allylcysteine

Abstract: Due to the multiple pathogens of Alzheimer's disease, multitarget-directed ligand (MTDL) design has been highly regarded in recent years. MTDLs are used to control several pathogens at the same time. The main objective of this research is to provide an appropriate MTDL for the treatment of Alzheimer's disease. Due to the high importance of cholinesterase inhibition, chelating metal ions and collecting free radicals in the treatment of Alzheimer's disease, we used bis(7)tacrine as an efficient inhibitor of chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(172 reference statements)
0
2
0
Order By: Relevance
“… 60 . The fundamental theory of this calculation was explained in detail in our previous publications 61 , 62 . In this study, the GROMACS trajectories were used to compute the affinity of the chosen ligands toward mTOR proteins by GMXPBSA 2.1.…”
Section: Methodsmentioning
confidence: 99%
“… 60 . The fundamental theory of this calculation was explained in detail in our previous publications 61 , 62 . In this study, the GROMACS trajectories were used to compute the affinity of the chosen ligands toward mTOR proteins by GMXPBSA 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, MD simulations of a survey of tacrine-huprine heterodimers revealed that derivatives show potential for AD and prion disease treatment because they both inhibit the PAS and CAS in AChE while reducing β-amyloid and prion peptide aggregation [ 96 ]. Other dimers that exhibit dual-site inhibitory activity with the cholinesterase enzymes are the bis(7)tacrine derivative with S-allylcysteine and cystamine, both of which can also serve as antioxidants [ 97 , 98 ]. The hybrid of tacrine and quercetin, dubbed Tac-Quer in a 2019 study by Habibpour et al, allows tacrine to act as an inhibitor to either AChE or BChE, while quercetin, a well-known metal scavenger, seeks Zn 2+ , Cu 2+ , and Fe 2+ cations in trace quantities in brain plaque [ 99 ].…”
Section: Inhibitionmentioning
confidence: 99%